PENERAPAN MEDIA INTERAKTIF BERBASIS POWTOON TERHADAP HASIL BELAJAR IPA PADA SISWA KELAS V UPT SD NEGERI 2 RAPPANG - Suci Pratiwi Tahir; Nadrah; Salwa Rufaida (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was motivated by the low learning outcomes of fifth-grade students inscience subjects at UPT SD Negeri 2 Rappang. One of the contributing factors isthe lack of variation in the learning media used by teachers, which causesstudents to feel bored and have difficulty understanding the material. This studyaims to analyze students science learning outcomes before and after theimplementation of interactive learning media based on Powtoon, and to determinewhether there is a significant difference following the treatment. This research isan experimental study using a One Group Pretest-Posttest Design. The subjectsconsisted of 20 fifth-grade students. Data were collected using a multiple-choicetest consisting of 30 items administered before and after the treatment. The datawere analyzed using descriptive and inferential statistics with the help of SPSSversion 25 software, employing the Paired Sample T-Test. The results of theanalysis showed an increase in the students’ average scores after using Powtoonas a learning medium. The significance value (2-tailed) was 0.000 < 0.05,indicating a statistically significant difference between the students learningoutcomes before and after the treatment. Therefore, it can be concluded that theuse of interactive learning media based on Powtoon has a positive impact onimproving science learning outcomes of fifth-grade students.